Geochemical Characterization of Insoluble Particle Clusters in Ice Cores Using Two‐Dimensional Impurity Imaging. (21st February 2023) - Bohleber, Pascal; Stoll, Nicolas; Rittner, Martin; Roman, Marco; Weikusat, Ilka; Barbante, Carlo
Abstract: Understanding post‐depositional processes altering the layer sequence in ice cores is especially needed to avoid misinterpretation of the oldest and most highly thinned layers. The record of soluble and insoluble impurities represents an important part of the paleoclimate proxies in ice cores but is known to be affected through interaction with the ice matrix, diffusion, and chemical reactions. Laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) has been recognized for its micron‐scale resolution and micro‐destructiveness in ice core impurity analysis. Employing LA‐ICP‐MS for 2D chemical imaging has already revealed a close relationship between the ice grain boundary network and impurity signals with a significant soluble component, such as Na and Mg. Here we show the latest improvements in chemical imaging with LA‐ICP‐MS, by increasing the spatial resolution to 20 μm and extending the simultaneous analysis to also mostly insoluble impurities, such as Al and Fe. All analytes reveal signals of dispersed spots in a sample of an East Greenland ice core. Based on their average size around 50–60 times larger than an average particle and their heterogeneous elemental ratios these spots are interpreted as particle clusters. To distinguish their origin, a simple colocalization classification reveals elemental ratios consistent with marine and mineral dust aerosol. Based on already existing data from cryo‐Raman spectroscopy, we discuss potential ways to integrate the two methods in a future comparison. Such a combined approach may help constraining post‐depositional changes to the dust‐related insoluble impurity components, such as cluster formation and chemical reactions at grain boundaries. Plain Language Summary: Aerosols of marine and terrestrial origin delivered to the polar ice sheets are archived in the ice and can be studied via the analysis of ice cores. The chemical composition and size of mineral dust can deliver important information about past climatic changes and atmospheric transport. However, it has already been shown that this insoluble material is not always passively archived in the ice but can undergo changes in its chemical composition and size, for example, by forming particle aggregates. To investigate these processes, it is preferable to study the chemical composition of insoluble particles and their localization within the ice matrix. Here we show how this can be done by a new chemical imaging method for ice using laser ablation inductively coupled plasma mass spectrometry. In a sample of a Greenland ice core we find clear signals of particle clusters, 50–60 times larger than a single particle. Based on their chemical composition, it is possible to differentiate between marine and terrestrial material. We discuss the results against findings previously obtained for the same sample from a different method, cryo‐Raman spectroscopy. Bringing together several methods may provide important added value for a more comprehensive understanding of these important indicators of past climate. Key Points: Laser ablation inductively coupled plasma mass spectrometry imaging investigates the geochemical composition and localization of particles in samples of the East Greenland Ice Core Project ice core, East Greenland The maps reveal clusters of insoluble particles 50–60 times larger than an average particle, at intra‐grain locations and grain boundaries Geochemical signals of the particles are consistent with cryo‐Raman spectroscopy and with known dust sources and sea salt aerosol